2018
DOI: 10.1021/acs.iecr.7b04554
|View full text |Cite
|
Sign up to set email alerts
|

A Quality-Related Statistical Process Monitoring Method Based on Global plus Local Projection to Latent Structures

Abstract: The partial least-squares (PLS) method is widely used in the quality monitoring of process control systems, but it has poor monitoring capability in some locally strong nonlinear systems. To enhance the monitoring ability of such nonlinear systems, a novel statistical model based on global plus local projection to latent structures (GPLPLS) is proposed. First, the characteristics and nature of global and local partial least-squares (QGLPLS) are carefully analyzed, where its principal components preserve the lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 31 publications
1
21
0
Order By: Relevance
“…9) integrates the advantages of PLS and LLE methods. The distinctive feature of the GPLPLS model is that the local nonlinear features are enhanced by LLE in the PLS decomposition (Zhou et al 2018). GPLPLS uses the strategy of plus but not embedding, in which the new feature space is divided into linear part (global projection) and nonlinear part (local preserving).…”
Section: Comparison Of Gplpls Lppls and Lleplsmentioning
confidence: 99%
“…9) integrates the advantages of PLS and LLE methods. The distinctive feature of the GPLPLS model is that the local nonlinear features are enhanced by LLE in the PLS decomposition (Zhou et al 2018). GPLPLS uses the strategy of plus but not embedding, in which the new feature space is divided into linear part (global projection) and nonlinear part (local preserving).…”
Section: Comparison Of Gplpls Lppls and Lleplsmentioning
confidence: 99%
“…Experiments showed that they are efficient and robust for the data with inherent uncertainty and outliers. However, the two improved RPCA methods do not obtain any useful information from the output quality variables, so it is difficult to directly apply them to quality-relevant process monitoring and fault diagnosis (Zhou et al 2018). The monitoring system will automatically alarm if a fault is detected whether it affects the product quality or not.…”
Section: Motivation Of Robust L 1 -Plsmentioning
confidence: 99%
“…To improve the efficiency of the LAD algorithm, the idea of partial least squares (PLS) regression is used to extend the conventional LAD regression to partial LAD regression. The PLS-based monitoring method decomposes the process space through the correlation between the quality and the process variables, which can reflect the quality-relevant product changes in the process variables (Wang et al 2017;Zhou et al 2018).…”
Section: Motivation Of Robust L 1 -Plsmentioning
confidence: 99%
“…For such applications, the data-driven process monitoring (DPM) methods are preferred due to their data-based characteristics, which do not require the accurate models of complex systems. [5][6][7] The DPM methods mainly implement the fault monitoring, the fault identification and diagnosis, the fault reconstruction and the product quality monitoring and control in the production process by making use of the multiple statistics process control (MSPC) and the machine learning methods, 8,9 which has been successfully applied to many industrial fields such as chemical industry, steel, electric power, and so on. [10][11][12] The partial least squares (PLS) is a significant MSPC method, which can be traced back to the nonlinear iterative partial least squares (NIPALS) path model method proposed by Wold and Lyttkens 13 to solve the problems of the model parameter estimation in econometrics and behavioral sciences.…”
Section: Introductionmentioning
confidence: 99%